The role of mTOR-mediated signals during haemopoiesis and lineage commitment. (28th August 2018) - Malik, Natasha; Sansom, Owen J.; Michie, Alison M.
Abstract : The serine/threonine protein kinase mechanistic target of rapamycin (mTOR) has been implicated in the regulation of an array of cellular functions including protein and lipid synthesis, proliferation, cell size and survival. Here, we describe the role of mTOR during haemopoiesis within the context of mTORC1 and mTORC2, the distinct complexes in which it functions. The use of conditional transgenic mouse models specifically targeting individual mTOR signalling components, together with selective inhibitors, have generated a significant body of research emphasising the critical roles played by mTOR, and individual mTOR complexes, in haemopoietic lineage commitment and development. This review will describe the profound role of mTOR in embryogenesis and haemopoiesis, underscoring the importance of mTORC1 at the early stages of haemopoietic cell development, through modulation of stem cell potentiation and self-renewal, and erythroid and B cell lineage commitment. Furthermore, the relatively discrete role of mTORC2 in haemopoiesis will be explored during T cell development and B cell maturation. Collectively, this review aims to highlight the functional diversity of mTOR signalling and underline the importance of this pathway in haemopoiesis.